Penerapan Model Pembelajaran Problem Based Learning san Pendekatan Saintifik Berbasis Lesson Study Untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa - Lisa Ariani; Asrin Lubis (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2024)
The purpose of this study is to ascertain how efforts are made and enhance students' capacity for problem-solving following the application of the lesson study-based scientific approach and problem-based learning model. 38 students from SMP Negeri 4 Tebing Tinggi's VIII–5 class during the 2022–2023 academic year served as the research subjects. Classroom Action Research (PTK), which is this kind of research, is divided into two cycles. In pre-action, students take an initial test, and at the conclusion of each cycle, they take an exam on their problem-solving skills. The research findings are as follows: (1) If the teacher masters and effectively applies the PBL model and scientific approach based on lesson study, students' mathematical problem solving abilities can be improved, (2) Application of the PBL model can increase student learning completeness by 63.16% from 23.68% at the end of cycle I to 86.84% at the end of cycle II. (3) Students' mathematical problem solving abilities can be improved by 34.37% from 47.47% at the end of cycle I to 82.04% at the end of cycle II.